Characterization of havan fume extract through GC-MS, molecular docking and antifungal activities - Vikash rana; Sanjay Kumar; Navneet Bithel (Environment Conservation Journal)
The act of performing havan is an ancient custom in India. Fire offering materials, which is composed of significant medicinal herbs and mango wood pieces, is traditionally used during havan. It purifies the air by lowering the burden of airborne microorganisms. This study examined the use of 31 plant constituents in the composition of fire offering materials and its fume potential function against airborne fungi. 58.98% and 38.77% maximum reduction of fungal CFU count were calculated between pre havan and post havan exposed plates inside and outside yagyashala respectively. Air  vacuum cleaner was first time used in our report to collect medicinal fume extract of fire offering materials and can also help in carbon nanodots extraction from havan fume in future prospects. The ethanolic and aqueous fume extract of fire offering material was tested against two air isolated fungi by  poisoned food method i.e. Curvularia lunata and Penicillium chrysogenum. The   ethanolic and aqueous fume extract of fire offering material showed maximum antifungal activity against Curvularia lunata and Penicillium chrysogenum  respectively. The GC-MS analysis of ethanolic extract showed 20 peaks of a bioactive compound with % peak area that revealed the maximum concentration of acetic acid (39.63%) followed by asarone (15.29%). Furthermore, a molecular docking study was used for first time to confirm the antifungal activity. The results indicate that the GC-MS compound asarone has a strong binding affinity with the melanin biosynthesis enzyme trihydroxy naphthalene reductase (PDB ID-1YBV), a significant virulence factor of Curvularia lunata, confirming its antifungal potential. The binding energy of asarone compound against Curvularia lunata protein 1YVB was reported – 6.3 kcal/mol.